Marine wildlife as an important component of coastal visits: The role of perceived biodiversity and species behaviour. (April 2017) - White, Mathew P.; Weeks, Abigail; Hooper, Tom; Bleakley, Luke; Cracknell, Deborah; Lovell, Rebecca; Jefferson, Rebecca L.
Abstract: Although the (perceived) biodiversity of a natural environment can influence people's actual, or predicted, restorative experiences, little is known about the generality of these effects or the importance of other aspects such as wildlife behaviour. The current research used an experimental approach (with photographs and videos of coastal scenes) to investigate these issues among a large heterogeneous UK sample (n=1, 478). On average, coastal settings with higher perceived biodiversity were rated as offering greater restorative potential and were associated with higher willingness-to-visit. Men, and people with lower overall ratings, tended to be more sensitive to biodiversity levels, and older respondents believed coastal settings in general offered more restorative potential. Locations where a species was exhibiting High vs. Low fascination behaviours (e.g. murmurating vs. sleeping) were also rated more positively, highlighting the importance of wildlife behaviour on psychological outcomes, in addition to biodiversity. Implications for conservation and communication are discussed. Highlights: Restorative potential of coastal locations was explored using photos/videos. Greater perceived biodiversity was associated with greater restorative potential. More fascinating behaviours were associated with more restorative potential. Willingness-to-visit was higher for locations with more fascinating behaviours. Men were more sensitive to biodiversity and behaviour than women.